Analysis of the Birt–Hogg–Dubé (BHD) tumour suppressor gene in sporadic renal cell carcinoma and colorectal cancer. Issue 11 (19th November 2003) - Fernandes da Silva, N; Gentle, D; Hesson, L B; Morton, D G; Latif, F; Maher, E R
Abstract : Germline mutations in the BHD gene cause the dominantly inherited cancer susceptibility disorder, Birt–Hogg–Dubé (BHD) syndrome. Individuals with BHD are reported to have an increased risk of renal cell carcinoma (RCC) and of colorectal polyps and cancer. The BHD gene maps to 17p11.2, and to investigate whether somatic inactivation of the BHD gene region is implicated in the pathogenesis of sporadic RCC and colorectal cancer (CRC), we performed mutation analysis in 30 RCC primary tumours and cell lines, and 35 CRCs and cell lines. A somatic missense mutation (Ala444Ser) with loss of the wild type allele (consistent with a two hit mechanism of tumorigenesis) was detected in a primary clear cell RCC, and a further missense mutation (Ala238Val) was identified in a clear cell RCC cell line for which matched normal DNA was not available. A somatic missense substitution (Arg392Gly) was identified in a primary CRC, and the same change was detected in three RCCs (all oncocytomas) for which matched normal DNA was not available. A germline Arg320Gln missense variant detected in a primary CRC was not detected in 40 control individuals or in a further 159 familial and sporadic CRC cases. However, AA homozygotes for an intronic single nucleotide polymorphism (c.1517+6 G→A) were under-represented in familial cases compared with controls (p = 0.03). For some tumour suppressor genes, epigenetic silencing is a more common mechanism of inactivation than somatic mutations. However, we did not detect evidence of epigenetic silencing of BHD in 19 CRC and RCC cell lines, and BHD promoter region hypermethylation was not detected in 20 primary RCCs. These findings suggest that BHD inactivation occurs in a subset of clear cell RCC and CRC.